Perlindungan KUH-Perdata dalam Pemutusan Sepihak pada Kontrak Kerja Tinjauan Fikih Muamalah : Civil Code Protection in Unilated Termination of Employment Contracts in Fikih Muamalah Review - Iskandar, Iskandar; M. Dzulfaldi S.; Srydewi Awaliani Syaputri (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, IndonesiaInstitut Agama Islam STIBA Makassar, Indonesia, 2024)
The legal protection of the Civil Code and muamalah jurisprudence is needed to answer and provide a solution to problems related to unilateral termination of employment relations by a company or limited liability company or individual that occurs in society. This research aims to analyze the protection provided by the Civil Code (KUH-Perdata) in the context of unilateral termination of employment contracts with a review of the principles of muamalah fiqh. The research results show: First, the Civil Code provides protection for workers affected by unilateral termination of employment contracts through various provisions that regulate workers' normative rights, including the right to income, benefits and protection against discrimination. Second, muamalah fiqh has several principles that are relevant in assessing the validity and justice of unilateral termination of an employment contract, such as justice, agreement, fair compensation, freedom of contract and must be carried out taking into account sharia principles, such as fairness, honesty and equality. Therefore, the parties involved in an employment contract must understand and respect each other's rights. Third, regarding the provisions of the Civil Code which regulate unilateral termination of employment contracts, it can be concluded that most of the principles of muamalah fiqh are reflected in Indonesian civil law. However, there is still room for increasing protection for workers in unilateral termination in accordance with the values ​​of muamalah fiqh.